Reading and Writing History in Sixteenth-Century France: The Case of La Legende des Flamens (1522). (1st December 2016) - Emerson, Catherine
A rare copy of a first edition of La Légende des Flamens, now in Trinity College Dublin, reveals a number of facts about its position in that library, probably a mid-nineteenth-century acquisition but acquired in the context of existing similar holdings of medieval and early modern French historical writings. Unlike these writings, however, the text takes an explicitly anti-Flemish and pro-French royalist stance. Criticism levelled at the two most recently deceased popes — or at the English — may explain why the author has decided to remain anonymous, or the text may have been conceived as a compilation of documentary sources without need for an author. This article examines the way that the text deploys sources, including a lost work by Giles of Rome, and draws some conclusions about the situation of the author of the text. Publisher François Regnault is considered as a possible author.